The The Relationship between Nutritional Status and Worm Infection with the Intellectual Ability: A Case of Children Aged 6-12 Years in Jungkat Village - Wolly Candramila, Wolly Candramila; Kurniati, Yulia; Mardiyyaningsih, Asriah Nurdini (Window of Health : Jurnal Kesehatan, 2025)
The prevalence of worm infection in Indonesia remains high, reaching 21.6% in 2022, with significant impacts on children, including decreased cognitive function and growth impairments. Theoretically, children who are in high-risk environments for worm infection and delayed growth have a high potential to have low intelligence. This study aimed to describe the nutritional status, worm infection, and intellectual ability of elementary school children in Jungkat Village, and to analyze the interrelationships between these factors. A cross-sectional study was conducted in four elementary schools in Jungkat Village from June to August. A total sampling approach was applied, with 626 children aged 6–12 years who met the inclusion criteria (enrolled in the schools and obtained parental consent). Data were collected via anthropometric measurements, a worm infection questionnaire, and Raven’s Progressive Matrices (RPM), and analyzed using multinomial logistic regression. More than 70% of children had a normal nutritional status, but stunting (20.78%), overweight (7.67%), and obesity (7.67%) indicated a dual burden of malnutrition. The prevalence of worm infection is notably high (29.71%), while intellectual assessments indicate that 60.86% of children fall into the below-average or defective categories. Interestingly, children in Jungkat Village appear to adapt to worm infections, as these do not seem to impair intellectual capacity. Despite having a mostly normal nutritional status, many individuals still demonstrate below-average intellectual abilities, suggesting that other determinants, beyond nutrition and infection, may play a stronger role. Further studies are recommended to explore genetic, environmental, and educational factors that may influence children’s intellectual development.